2015
DOI: 10.1002/anie.201501434
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Walled Carbon Nanotube/Metalloporphyrin Composites for the Chemiresistive Detection of Amines and Meat Spoilage

Abstract: Abstract:Chemiresistive detectors for amine vapors were made from single-walled carbon nanotubes by non-covalent modification with cobalt meso-arylporphyrin complexes. We show that through changes in the metal's oxidation state, the electron-withdrawing character of the porphyrinato ligand, and the counteranion, the magnitude of chemiresistive response to ammonia could be improved. The devices exhibited sub-ppm sensitivity and high selectivity toward amines as well as good stability to air, moisture, and time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
100
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(110 citation statements)
references
References 30 publications
8
100
0
2
Order By: Relevance
“…Although other sensing mechanisms have been reported, such as swelling of the SWCNT network or the junctions between electrode and SWCNT, electron transfer has been shown as the dominant factor in the majority of porphyrin-based SWCNT sensors. [13,44,49] In conclusion, we developed an amperometric platform for the detection of CO with voltagemodulated sensitivity using the bio-inspired interaction between CO and iron porphyrin. We demonstrate the importance of installing covalent pyridyl ligands on the SWCNTs for localizing and electronically coupling the iron porphyrins to the carbon nanotubes.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Although other sensing mechanisms have been reported, such as swelling of the SWCNT network or the junctions between electrode and SWCNT, electron transfer has been shown as the dominant factor in the majority of porphyrin-based SWCNT sensors. [13,44,49] In conclusion, we developed an amperometric platform for the detection of CO with voltagemodulated sensitivity using the bio-inspired interaction between CO and iron porphyrin. We demonstrate the importance of installing covalent pyridyl ligands on the SWCNTs for localizing and electronically coupling the iron porphyrins to the carbon nanotubes.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…Single-walled carbon nanotube (SWCNT) chemiresistors and chemical field effect transistors (Chem-FET) have been shown to provide suitable platforms for the detection of various gases. [10][11][12][13][14][15] Random networks of functionalized SWCNTs have produced sensors that are inexpensive to fabricate, operate at room temperature, and have ultra-low power requirements. [16,17] Theoretical and experimental reports have suggested that CO does not engage in charge transfer with pristine SWCNTs, [18][19][20] indicating the a chemical reactive interface is necessary.…”
mentioning
confidence: 99%
“…3 Their mechanical properties are already exploited in a variety of commercial applications, 4 and examples of advanced SWNT-based electronic devices are being developed. 510 The chemical modification of SWNTs can tune their properties and/or improve their processability. To this end, both covalent and supramolecular approaches have been extensively explored.…”
Section: Introductionmentioning
confidence: 99%
“…The innate sensitivity of organic semiconductors to amine vapours [2][3][4][5][6][7][8][9] translates to water-borne amines. We demonstrate this with the help of water-gated PBTTT OTFTs, which respond with a reduced drain current when octylamine is added to the gating water.…”
Section: Discussionmentioning
confidence: 99%
“…Resistivity substantially increased under odour exposure due to the de-doping of the acid-doped PAni by the amine acting as a Lewis base. Similarly, Hague et al [3] demonstrated an organic transistor-based sensor for amine odours where a previously undoped n-type organic semiconductor was doped by amine odours, with consequential impact on transistor characteristics [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%